Gambaran Bentuk Distorsi Kognitif pada Pelaku Kekerasan Seksual Inses - Latief, Raudyatuh Zahra; Tajuddin, Istiana; Amal, Andi Juwita (Fakultas Psikologi Universitas Sanata Dharma, 2024)
Incest is sexual contact that occurs between families who are related by blood. Incest includes an act of sexual violence when there is no consent from the victim. This research aims to obtain an overview of the forms of cognitive distortion of incest perpetrators against the child. This research was carried out using a qualitative case study approach with in-depth interviews based on cognitive distortion theory. Participants in this research were the biological fathers of 3 victims. Data analysis was carried out using a theory-led approach or coding the interview results based on the theory of the forms of cognitive distortion of perpetrators of sexual violence. The data analysis process is assisted by the MaxQDA application. The results of this research indicate that cognitive distortions encourage perpetrators to commit acts of incestuous sexual violence against their biological children. In line with cognitive distortion theory, there are 5 forms of cognitive distortion found in participants, namely uncontrollable (the perpetrator's inability to control himself), nature of harm (sexual relations are considered harmless), children as sexual beings (children are interested in sexual relations), dangerous world (the perpetrator views adults as dangerous) and entitlement (parents' rights to children). The event that initiated incest was the perpetrator's wife's refusal to have sexual intercourse. Disharmony in the participant's family was also caused by family functions not running well, such as religious, economic, as well as educational and socialization functions. Therefore, this research has implications for the development of further research that can focus on family functions that cause incest.